A review of nanostructured delivery systems for the encapsulation, protection, and delivery of silymarin: An emerging nutraceutical. (June 2022) - Zhang, Zhiheng; Li, Xiaojing; Sang, Shangyuan; McClements, David Julian; Chen, Long; Long, Jie; Jiao, Aiquan; Wang, Jinpeng; Jin, Zhengyu; Qiu, Chao
Graphical abstract: Highlights: The development of nano-delivery systems is a potential solution of functional foods. The green preparation methods of silymarin-loaded nanocarriers were reviewed. Biopolymer-, lipid-, surfactant-, and other based nanocarriers were discussed. Edible nanocarriers can improve the stability and bioavailability of silymarin. The potential of nanocarriers to improve the bioactivity of silymarin was discussed. Abstract: Silymarin exhibits biological activities that may promote human health and wellbeing, including antioxidant, antimicrobial, anti-inflammatory, and anti-cancer activities. Consequently, it has potential for application as a nutraceutical ingredient in functional foods and supplements. But its application for this purpose is currently limited by its poor water solubility, chemical stability, and bioavailability. The potential of nano-delivery systems to improve the functional performance of silymarin was reviewed in this manuscript. The formation, attributes, and applications of biopolymer-based, lipid-based, surfactant-based, and miscellaneous nanocarriers are discussed. In particular, the impact of the different delivery systems such as biopolymer-based, lipid-based delivery systems on the gastrointestinal fate of silymarin is summarized. The encapsulation in edible nanocarriers can improve the bioavailability of silymarin by enhancing its water-dispersibility, inhibiting its degradation, and increasing its absorption. These nanocarriers may therefore be utilized to incorporate this nutraceutical into functional foods and supplements in a bioavailable form.